2018
DOI: 10.1021/acs.joc.7b02595
|View full text |Cite
|
Sign up to set email alerts
|

Allylic C–S Bond Construction through Metal-Free Direct Nitroalkene Sulfonation

Abstract: A metal-free, open-flask protocol was developed for the preparation of allylic sulfones through direct condensation of sodium arylsulfinates and β,β-disubstituted nitroalkenes. The key step of this process was the Lewis base-promoted equilibrium between nitroalkenes and allylic nitro compounds. Through this process, the readily available conjugated nitroalkenes can be easily converted into allylic nitro compounds, which contain more reactive C═C bonds toward the sulfonyl radical addition. As a result, allylic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 75 publications
0
17
0
Order By: Relevance
“…Lei et al reported a metal-free direct denitro-sulfonylation reaction between β,β-disubstituted nitroalkenes and sodium arylsulfinates to give allyl sulfones ( Scheme 122 ). 186 The iodine-catalyzed direct condensation of both reactants of β,β-disubstituted nitroalkenes and sodium arylsulfinates bearing electron-donating and electron-withdrawing groups was successfully explored in this protocol. An array of allyl sulfones was obtained in good to high yields with high selectivity.…”
Section: Applications Of Sodium Sulfinatesmentioning
confidence: 99%
“…Lei et al reported a metal-free direct denitro-sulfonylation reaction between β,β-disubstituted nitroalkenes and sodium arylsulfinates to give allyl sulfones ( Scheme 122 ). 186 The iodine-catalyzed direct condensation of both reactants of β,β-disubstituted nitroalkenes and sodium arylsulfinates bearing electron-donating and electron-withdrawing groups was successfully explored in this protocol. An array of allyl sulfones was obtained in good to high yields with high selectivity.…”
Section: Applications Of Sodium Sulfinatesmentioning
confidence: 99%
“…In 2018, the direct condensation of sodium arylsulfinates and β,β-disubstituted nitroalkenes for the preparation of allylic sulfones was realized by Chen group. [28] The Lewis basepromoted equilibrium between nitroalkenes and allylic nitro compounds was the key step for this reaction. The desired products can be isolated in a high selectivity and yield.…”
Section: Sulfonylation/noncyclization With Alkenesmentioning
confidence: 99%
“…In the light of these three discoveries, Shi and Chen observed a very different reaction outcome when α-substituted nitrostyrenes 1 reacted with the sodium salt of aryl sulfinic acids 23 ( Scheme 20 ) [ 61 ]. Unlike in the previous reports, the reaction between sodium sulfinic acid salt and the nitroolefin yielded allylic sulfones instead of the conjugated sulfones.…”
Section: Nitrostyrenes In Denitrative C(sp 2 )-mentioning
confidence: 99%